A genetic algorithm based on spatiotemporal conflict between continuous berth-allocation and time-varying specific crane assignment. Issue 3 (4th March 2019) - Yu, Tian; Qiang, Zhou; Benfei, Zhu
ABSTRACT: Berths and quay cranes (QCs) are two important resources in container terminals. Although good planning can shorten ship turnaround times, berths and QCs are interdependent. In the handling process, the number of QCs assigned to a ship may vary because of other ships berthing or departing. This variation, in turn, affects the QCs' efficiency and the ship handling time, thus affecting the following ships' berth–QC planning. In this article, a new mixed-integer programming model for simultaneous continuous berth-allocation and time-varying specific QC assignment is established. Furthermore, a genetic algorithm based on spatiotemporal conflict is designed for the model. Numerical experiments show that the proposed method can provide a reasonable solution for such an NP-hard problem in a reasonable time. In addition, the important parameters affecting the results are analysed.